Accidental and Intentional Exporters: Comparing Indonesia and Malaysia MSMEs - Tham Siew Yean; Tulus Tambunan (International Journal of Small and Medium Enterprises and Business Sustainability, 2018)
Both Indonesia and Malaysia seek to enhance the competitiveness of their micro, small and medium enterprises (MSMEs) by including internationalization goals in their respective national development plans for these enterprises. In this respect, there are some important questions, namely how do MSMEs in these two countries penetrate the external market, including the ASEAN market? What are the policies and institutions that have enabled them in their internationalization attempts? This study seeks to answer these questions by using an analytical framework that combines the stages, network and international new ventures theory as well as policy and institutional support, to investigate several case studies in Indonesia and Malaysia. The case study approach is used to provide richer and deeper insights into the internationalization journey of MSMEs in Indonesia and Malaysia. Semi-structured interviews based on the same analytical framework are used in both countries’ cases. The cases are chosen based on the companies’ willingness to be interviewed from a list of exporting MSMEs provided by the relevant government agencies in each country. The findings from the 14 case studies in the two countries indicate that exporting may be a serendipitous discovery for most of the cases as few are born global in intent. Shifting to intentional exporting will require entrepreneurs to have the vision to do so and to be able to implement the vision by tapping into government and/or private networks to connect firms with international buyers.